Brand Personality Selebriti Sebagai Strategi Komunikasi Krisis - Almira Shabrina; Rah Utami Nugrahani; Shafina Nasywa; Atala Aminia (Jurnal Riset Komunikasi (JURKOM), 2024)
The use of TikTok social media has made iced tea one of the drink brands that has become the top of mind for grab and go drinks in Indonesia. However, like a double-edged sword, the use of social media is one of the causes of problems that can lead to a bad reputation in the eyes of consumers. To prevent the Company's Image from getting worse, Es Teh Indonesia replaced the Chief Executive Officer who is now held by Nagita Slavina. For this reason, this research looks at how Nagita Slavina's brand personality as a crisis communication strategy. This study uses a descriptive qualitative research method to see how this CEO turnover phenomenon becomes an image for Indonesian iced tea. Researchers conducted research on six Generation Z informants who live on the island of Java and consume Indonesian iced tea more than 6 times. The results of the study show that Nagita Slavina's brand personality is less effective in handling the crisis management that has been carried out by Es The Indonesia. Keywords: Brand Personality; Crisis Management; Es Teh Indonesia